Diversity and ecological characteristics of the vascular flora in the Western Mediterranean (Eastern Andalusia, Spain). Diversidad y características ecológicas de la flora vascular en el Mediterráneo Occidental (Andalucía Oriental, España) - Cueto, Miguel; Blanca, Gabriel; Salazar, Carlos; Cabezudo, Baltasar (Acta Botanica Malacitana, 2014)
This work highlights the importance of the vascular flora of eastern Andalusia within the hotspot of the Mediterranean Basin, analysing 3726 taxa, which represent 42.0% of the Iberian Peninsula and 29.9% of European floras. Notably, 10.3% of the flora is endemic (350 taxa), constituting 34.3% of the endemism of the Iberian Peninsula and Balearic Islands, and 2.6% of those of the Mediterranean Basin, which include 6 of the 17 endemic genera of the Iberian Peninsula and Balearic Islands, 3 of these being exclusive of the territory analysed. Chamaephytes and hemicryptophytes make up 45.5% of the flora, with decreasing values for the therophytes as altitudes rise (41.1-8.1%) and increasing values for hemicryptophytes (22.4%-63.2%). Mediterranean taxa comprise 39.2%, followed by Ibero-North African taxa (15.3%), Iberian (13.9%), European (11.3%) and local endemism (9.4%). Of these taxa, 12.5% are threatened, according to the criteria of the UICN. Tanacetum funkii, exclusive of this area, is considered extinct. Only 6 families account for 43.5% of the threatened taxa. The Mesomediterranean thermotype (600-1400 m a.s.l.) harbours 82.8% of the species, with a maximum of between 700-800 m a.s.l. and with two zones of minimums: from -100 to 0 m a.s.l. and from 3300 to 3400 m a.s.l.